A comprehensive review of Mycoplasma pneumoniae infection in chronic lung diseases: recent advances in understanding asthma, COPD, and bronchiectasis - Guo, Zai-qiang; Gu, Shun-yi; Tian, Zhi-hua; Du, Bo-ying (Frontiers in Medicine, 2024)
This review summarizes the research progress over the past 30 years on the relationship between Mycoplasma pneumoniae infection and chronic respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), and bronchiectasis. Mycoplasma pneumoniae is a common cause of community-acquired pneumonia, particularly in children and young adults. Key findings from recent studies indicate that M. pneumoniae infection is associated with a higher risk of asthma exacerbations and may contribute to the development of bronchiectasis in susceptible individuals. Additionally, emerging evidence suggests that M. pneumoniae-induced immune dysregulation plays a crucial role in the pathogenesis of chronic lung diseases. This review aims to summarize the current understanding of the potential links between M. pneumoniae pneumonia and various chronic respiratory conditions, including asthma, chronic obstructive pulmonary disease (COPD), and bronchiectasis. We discuss the epidemiological data, pathogenic mechanisms, clinical manifestations, and long-term consequences of M. pneumoniae-related respiratory illnesses. Additionally, we highlight the challenges in diagnosis and treatment, as well as future research directions in this field.